Economic burden of respiratory syncytial virus disease in Latin America: A systematic review - Carolina Moreno; Ariel Bardach; María Carolina Palermo; María Macarena Sandoval; Elsa Baumeister; Silvina Ruvinsky; Rolando Ulloa-Gutiérrez; Katharina Stegelmann; Sofía Ardiles Ruesjas; Jorge LaRotta; Rodrigo Sini de Almeida; Agustín Ciapponi (Human Vaccines & Immunotherapeutics)
This Systematic Review assesses the economic impact of Respiratory Syncytial Virus (RSV) in Latin America and the Caribbean (LAC) in relation to healthcare resource utilization and associated costs. We searched online databases from January 2012 to November 2022 to identify eligible publications. We identified 12 publications that reported direct costs, indirect costs, and resources associated with RSV and its complications. The primary direct medical resources reported were medical services, diagnostics tests and procedures, and length of stay (LOS). Direct total costs per patient ranged widely from $563 to $19,076. Direct costs are, on average, 98% higher than indirect costs. Brazil reported a higher total cost per patient than Colombia, El Salvador, México, Panamá, and Puerto Rico, while for indirect costs per patient, El Salvador and Panamá had higher costs than Brazil, Colombia, and Mexico. The mean LOS in the general ward due to RSV was 6.9 days (range 4 to 20 days) and the mean Intensive Care Unit LOS was 9.1 days (range 4 to 16 days). In many countries of the LAC region, RSV represents a considerable economic burden on health systems, but significant evidence gaps were identified in the region. More rigorous health economic studies are essential to better understand this burden and to promote effective healthcare through an informed decision-making process. Vaccination against RSV plays a critical role in mitigating this burden and should be a priority in public health strategies.